(untitled) (Revista Contexto & Educação, 2025)
This study aims to develop alternatives to support children and young people diagnosed with dyslexia, with an emphasis on fostering phonological awareness and improving the reading process. The research analyzes the application of the educational software EstimuGAME, designed to promote phonological stimulation through interactive and playful games. The study began in 2024 with eight eleven-year-old students from the municipal education network of Cerro Largo who participate in Specialized Educational Assistance (AEE) and will continue throughout 2025. The theoretical framework is based on authors such as Almeida (2009), Castrillon (2013), Condemarin (1986), Dehaene (2012), Magri Filho (2011), Martins (2003), Moojen (2014), Petrossi (2004), Sampaio (2011), and Snowling (2013). The methodology involves applying tests through oral readings before and after using the software, allowing for an assessment of its effectiveness in learning. Preliminary data collected in 2024 indicate progress in the reading skills of most participants, suggesting that the use of playful tools can be a valuable resource for the inclusion and development of students with dyslexia.